Integrating Metabolomics and Network Pharmacology to Explore the Protective Effect of Ginsenoside Re against Radiotherapy Injury in Mice. (11th March 2022) - Yu, Chunmiao; Fu, Jiaqi; Guo, Lidong; Yu, Miaomiao; Yu, Donghua
Abstract : Ionizing radiation (IR) can cause radiation damage, mutagenesis, or carcinogenesis in the irradiated subject. It is manifested as metabolic disorders of the body and damage to the immune system, nervous system, and endocrine system, which can lead to physiological and pathological changes and endogenous metabolic disorders. Ginsenoside Re (G-Re), a single component of traditional Chinese medicine, has a certain ameliorating effect on radiation damage. However, its mechanism of action in the treatment of radiotherapy injury remains unclear. With this purpose, the hematopoietic function of mice damaged by X-ray radiation was studied, and the protective effect of G-Re on mice damaged by radiation was preliminarily evaluated. Network pharmacology and metabolomics analysis are used to further reveal the mechanism of G-Re to improve radiation damage through metabolomics research. Results of metabolomics analysis showed that 16 potential biomarkers were identified as participating in the therapeutic effect of G-Re on IR. Most of these metabolites are adjusted to recover after G-Re treatment. The pathways involved included glycerophospholipid metabolism, sphingolipid metabolism, and linoleic acid metabolism. According to network pharmacology analysis, we found 10 hub genes, which is partly consistent with the findings of metabolomics. Further comprehensive analysis focused on 4 key targets, including SRC, EGFR, AKT1, and MAPK8, and their related core metabolites and pathways. This study combines metabolomics and network pharmacology analysis to explore the key targets and mechanisms of G-Re in the treatment of IR, in order to provide new strategies for clinical treatment of radiotherapy injury.